The wheeler dealers - Smith, Adam 1930-2014; Wallach, Ira 1913-1995 (Warner Home Video, 2011)
A Texas oilman heads to Wall Street to raise cash and meets a blonde stock analyst with her own angle
Orig., USA 1963
Widescreen format
Mono, widescreen 2.4:1
Keywords: Filmkomödie; Goodman, George J. W. / 1930-2014 / Film adaptations; Man-woman relationships / Drama; Stocks / Prices / Drama; Stocks / Prices; Man-woman relationships; Drama; Comedy films; Feature films; Fiction films; Film adaptations; Films comiques; Films de fiction; Adaptations cinématographiques; Film; DVD-Video